Quantitative measurements of backside wear in acetabular hip joint replacement: conventional polyethylene versus cross-linked polyethylene - Braun, Steffen; Jäger, Sebastian; Sonntag, Robert; Schröder, Stefan; Kretzer, Jan Philippe (Materials, 2020)
As shown in previous studies, the modification of conventional polyethylene (CPE) to cross-linked polyethylene (XLPE) and the contribution of antioxidants result in a reduction in total wear. The aim of this study was to evaluate XLPE inserts with vitamin E and CPE regarding their resistance to the backside wear mechanism. A cementless hip cup system (Plasmafit® Plus 7, Aesculap) was dynamically loaded using CPE and XLPE inserts. The backside wear was isolated, generated and collected using the two-chamber principle. The chambers were filled with ultrapure water. After 2 × 106 cycles, the fluids were examined for wear particles according to a particle analysis. Using XLPE inserts, the backside wear was significantly reduced by 35%. While XLPE backside wear particles are significantly larger than CPE particles, they do not differ in their morphology. This study confirms the greater resistance to backside wear of XLPE compared to CPE. It can be assumed that the improved fatigue resistance of the vitamin E-stabilized XLPE inserts demonstrates XLPE’s effectiveness against micro-motion and the resulting changing tensions in interface areas like surface breakdown, pitting and the release of very small particles.
Gesehen am 03.07.2020